Rekomendasi Obat Mabuk Perjalanan Bagi Traveller Dengan Menerapkan Metode OCRA Dan Pembobotan Metode ROC - Robiah Al-Adawiyah; Kevin Maulana Putra; Lastri Manik; Fince Tinus Waruwu (STMIK Budi Darma, 2022)
Traveling is a very pleasant thing, but traveling is really bad if the Traveler has motion sickness. So that the trip can be enjoyed more, travelers should drink or use anti-motion sickness drugs. There are several recommendations for anti-motion sickness drugs for travelers, such as: Dimenhydrinate, Antimo Strip, Tolak Angin, Dramamine, Promethazine, and Ondansetron. There are many anti motion sickness drugs circulating in the market today, so in this case a decision support system is needed to determine which anti motion sickness drugs are good for consumption by all groups, in determining them there are several alternatives and criteria including Certificates and Permits, Content, Dosage , contraindications, and side effects. A decision support system is needed in determining the best recommendations for motion sickness drugs with a combination of the ROC (Rang Order Centroid) method to produce weight values for certain criteria and the OCRA (Operational Competitiveness Rating Analysis) method which produces the best preferences based on data such as alternatives and criteria. which has been determined, then produces the best preference value in the 3rd alternative, namely Reject Wind with a final preference value of 1.2725 as the best alternative.